The shadow of war : Russia and the USSR, 1941 to the present - Lovell, Stephen, 1972- (Chichester, West Sussex, U.K. ; Malden, Mass. : Wiley-Blackwell, 2010)
"After enduring untold suffering and near total devastation, the Soviet Union emerged from the ashes of World War 2 as a superpower. Even now, the Great Patriotic War constitutes the country's single greatest source of national pride and identity--a defining moment in Russian history no less significant than the Revolution of 1917. Yet just as the overthrow of Tsarist autocracy is fraught with ambiguities, so too is the legacy of World War 2. After liberating itself from Nazi occupation, the Soviet Union established imperial domination over much of East-Central Europe. But a victorious Soviet society was also poor, hungry, and--for all intents and purposes--still enslaved by the communist regime. The shadow of war : the Soviet Union and Russia, 1941 to the present offers a fresh approach to modern Soviet and Russian history. Taking the achievements, ambiguities, and legacies of the Second World War as a point of departure, the book reveals the strains of the Soviet system in the postwar decades as it distanced itself from Stalinist repression and reinvented itself as a form of illiberal modern welfare state. The author shows how tens of millions of people moved from villages to cities to reap the benefits of modern civilization while Soviet society remained divided along strict class, regional, and ethnic lines--divisions that drew into sharp focus with the collapse of the Soviet Union. Utilizing the latest research and a wide range of sources, The shadow of war greatly enhances our understanding of Soviet and Russian history during one of the most complex and fascinating eras of human history"--Provided by publisher.
Introduction: World War II and the remaking of the Soviet Union -- Reform, reaction, revolution -- From plan to market -- Structures of society -- Public and private -- Centre and periphery -- National questions -- Geopolitical imperatives -- From isolationism to globalization.
Includes bibliographical references (p. [320]-354) and index.
Keywords: World War, 1939-1945 -- Influence; Soviet Union -- History -- 1939-1945.; Soviet Union -- History -- 1925-1953.; Soviet Union -- History -- 1953-1985.; Soviet Union -- History -- 1985-1991.; Russia (Federation) -- History -- 1991-